A Hitchhiker’s Guide to the Turing Galaxy: On naming the age of the networked digital computer - Grassmuck, Volker (Contemporanea, 2009)
The most commonly used name for our era is that of the `information society,`which is a rather unexpressive and, strictly speaking, tautological term. The informatics & society scholar Wolfgang Coy, following the example of McLuhan`s Gutenberg Galaxy, has introduced the concept of the Turing Galaxy. The paper retraces the pre-history of the concept, its grounding in the fundamental breakthroughs of the British mathematician Alan M. Turing, the Turing Machine and the Turing Test, analyses the reception of the concept in a variety of fields of scholarship and asks for its value in the further debate on the knowledge environment of the networked computer.